The Hermeneutics of Arūnas Sverdiolas - Mickevičius, Arūnas (Problemos, 2020)
The article seeks to highlight and thus draw attention to some important features of A. Sverdiolas’s thinking and his hermeneutic research. The article discusses three models of cultural hermeneutics: “weak hermeneutics,” “strong hermeneutics,” and “deep hermeneutics.” The aim of the article is to substantiate the thesis that A. Sverdiolas’s hermeneutics can be assigned to the so-called “strong hermeneutics,” but with elements that are also characteristic of the so-called “deep hermeneutics.” The article emphasizes that A. Sverdiolas considers and discusses in his texts the conceptual approaches of the so-called “weak hermeneutics,” but does not theoretically engage in it. It should be emphasized that A. Sverdiolas considers and discusses the conceptual approaches of the so-called “weak hermeneutics,” but does not theoretically engage in it. Also, based on the metaphorical image of “urbanization,” the article seeks to draw attention to A. Sverdiolas’s contribution to expanding and deepening research in the field of culture in Lithuania.
Keywords: Arūnas Sverdiolas; Hans-Georg Gadamer; strong hermeneutics